Pengaruh Beban Tugas Rumah dan Jam Belajar Panjang terhadap Stres Belajar - Ayu Lestari; Aisyah Alqurani; Risa Angelia; Sara Eriza; Nabila Deswina Fendri; Syahrizal Syahrizal (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
This study aims to analyze the effect of homework load and extended study hours on students’ learning stress levels. The background of this research is based on increasing academic demands that may affect students’ psychological conditions. This study employs a qualitative approach with data collected through observation and interviews. The results indicate that excessive homework load and prolonged study duration significantly contribute to higher levels of learning stress. Students tend to experience physical and mental fatigue, decreased motivation, and difficulty managing time between study and rest. In addition, pressure to achieve high academic performance further exacerbates stress levels. Other factors such as lack of environmental support and less varied teaching methods also influence students’ stress. Furthermore, students often report feelings of anxiety and emotional exhaustion when academic tasks accumulate without adequate rest periods. This condition not only affects their psychological well-being but also reduces concentration and learning effectiveness in the classroom. Therefore, balanced learning load management, appropriate task distribution, and more effective and humanistic teaching strategies are needed to reduce learning stress and improve the quality of education. Schools and educators are encouraged to consider students’ cognitive capacity and mental health in designing assignments and study schedules to create a more supportive learning environment.